Conversor CC/CA de alta freqüência baseado em inversores ressonantes com comutação seqüencial para excitação de uma tocha indutiva a plasma térmico - Dubut, Jean Paul (2010)
This work describes the study, the analysis, the project methodology and the constructive details of a high frequency DC/AC resonant series converter using sequential commutation techniques for the excitation of an inductive coupled thermal plasma torch. The aim of this thesis is to show the new modulation technique potentialities and to present a technological option for the high-frequency electronic power converters development. The resonant converter operates at 50 kW output power under a 400 kHz frequency and it is constituted by inverter cells using ultra-fast IGBT devices. In order to minimize the turn-off losses, the inverter cells operates in a ZVS mode referred by a modified PLL loop that maintains this condition stable, despite the load variations. The sequential pulse gating command strategy used it allows to operate the IGBT devices on its maximum power limits using the derating and destressing current scheme, as well as it propitiates a frequency multiplication of the inverters set. The output converter is connected to a series resonant circuit constituted by the applicator ICTP torch, a compensation capacitor and an impedance matching RF transformer. At the final, are presented the experimental results and the many tests achieved in laboratory as form to validate the proposed new technique